If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 19 = 19 + 6 Reorder the terms: 19 + x = 19 + 6 Combine like terms: 19 + 6 = 25 19 + x = 25 Solving 19 + x = 25 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-19' to each side of the equation. 19 + -19 + x = 25 + -19 Combine like terms: 19 + -19 = 0 0 + x = 25 + -19 x = 25 + -19 Combine like terms: 25 + -19 = 6 x = 6 Simplifying x = 6
| 5x-88+x*(x-65)=8888 | | 5x-88+x*(x-65)=8 | | 5x-88+x*(x-5)=8 | | x+14=17-19 | | 5/9(-37.8) | | x^2-4x+5=1 | | -14+2=x-1 | | (2x-1)=3 | | z+3/z-7=8/-3 | | -15=2x+3x | | .75=2x+9 | | 95-5x=22x+23 | | 2x+9=1.5 | | x-17=1-2 | | -55-9=9x+17 | | X^2-96x+256=0 | | x-11=9-10 | | d-6=7 | | x+6+x+9+x+3=x+1+x+1+x+4+x+4 | | 1.5b(3)=36 | | x/4+x/12=8 | | -8+4=x+6 | | -1/2x=23 | | y=17x^2+23x+19 | | -9-7=x-2 | | -5(-9z+13)=7(5z+19)-8 | | 9x-4=2x+78 | | 19g=-2(-4g-11) | | (1/16x^-8)^-1 | | -6(-9w-5)=-4(-12w-18) | | 75+39.95x=39.95x | | -6(4f-20)+15=-9f |